Antioxidant Properties and Potentiality of Silver Nanoparticles Biosynthesis of Thirty-Five Edible Bangladeshi Fruits (Bangladesh Journal of Botany, 2021)
A comparison of total polyphenols (TP) and flavonoids (TF) contents, antioxidant activity, and silver nanoparticles (AgNPs) biosynthesis potentiality of 35 common edible fruits in Bangladesh were studied. Among the fruits, Emblica officinalis showed the highest content of TP (89 mg gallic acid equivalent (GAE)/g powder), reducing power (OD, 1.98 at 1 mg powder/ml), and 2,2-diphenyl-1-picrylhydrazyl (DPPH)-free radical scavenging activity (95.6% at 0.5 mg powder/ml) whereas the highest content (17.3 mg (+)-catechin equivalent (CE)/g powder) of TF was recorded in Garcinia cowa. The inhibitory concentration 50 (IC50) for DPPH-free radical scavenging of Annona reticulata, E. officinalis, G. cowa, Phoenix sylvestris, Psidium guajava and Syzygium cumini were 180, 21.8, 172, 188.9, 162.4 and 176.2 μg powder/ml, respectively. Litchi chinensis showed the highest total antioxidant capacity (79 mg GAE/g powder) followed by E. officinalis (69 mg GAE/g powder). The fruits showed a very strong correlation (r2 = 0.99) between TP and reducing power. P. guajava showed the highest potentiality (OD, 0.74 at 10 mg powder/ml) in the biosynthesis of AgNPs followed by S. cumini, A. reticulata and P. sylvestris. Therefore, most potential five fruits should be graded as E. officinalis > S. cumini > P. guajava > A. reticulata > P. sylvestris.Bangladesh J. Bot. 50(3): 445-451, 2021 (September)